Sinais de risco psíquico em bebês na faixa etária de 3 a 9 meses e sua relação com variáveis obstétricas, sociodemográficas e psicossociais - Roth, Antônia Motta (2016)
This work started from a question about the possibility of early detection of psychological risk from a psychoanalytic perspective in an early age, considering the child's development as a global phenomenon in which the psychic is one of the structural pillars (Coriat; Jerusalinsky , 1996). In this perspective, a qualitative and quantitative research was developed, whose three main objectives were to analyze the frequency of psychological risk or risk to development in a sample of infants, comparing them as gestational age (preterm versus full term birth); analyze and relate the results obtained through IRDI and PREAUT protocols; and investigate possible associations between the presence of psychological risk and obstetric, psychosocial and sociodemographic factors. To this end, we evaluated 80 infants, 25 preterm and 55 full term between three and nine months of age, in order to assess the presence or absence of psychological risk from the application of both protocols and family interviews. Regarding PREAUT signs assessment at four months of age, it was found that 15 premature infants (60%) and 27 full term infants (49%) had at least one missing PREAUT signal. And in the PREAUT evaluation at nine months, the number was reduced to six premature infants (24%) and eleven full term infants (20%) with at least one missing PREAUT signal. Among the obstetric, psychosocial and sociodemographic variables that were statistically significant for the outcome presence of at least one missing PREAUT signal, we found: prematurity, baby s gender, presence of baby feed difficulties, the baby been able to explore their body and the environment around, the mother (or who exercises the maternal role) has a spouse that support her and she has any kind of professional activity. As for IRDls applied at three different times, we obtained different frequencies in each phase. In Phase I, it was obtained a frequency of 14 premature infants (56%) and 25 full term infants (45.45%) with at least one IRDI absent; in phase II, the values reduced to eleven premature infants (44%) and thirteen term infants (23.64%); and in phase III, the frequency was six premature infants (24%) and eleven term infants (20%) with at least one IRDI absent. Among the obstetric, psychosocial and sociodemographic variables that were related to the absence of IRDls: the Apgar of the 1', the baby s gender, breastfeeding until the sixth month of life, with whom the child sleeps (co-sleeping), maternal age, the mother (or who exercises the maternal role) has a spouse who support her and if her has any professional activity. Furthermore, it was found from the kappa factor that the two protocols showed a high level of agreement using different phenomenal signals to evaluate the presence of psychological risk. This research revealed that there is a positive correlation between the presence of psychological risk and child development in relation to obstetric, psychosocial and sociodemographic variables. also revealed the need of using both protocols in babies evaluations because they check different phenomenal signs to see the risk to child development beyond the psychological risk.